New enantioselective synthesis of antiobesity drug lorcaserin - Ghotekar, Ganesh S.; More, Devidas A.; Nalla, Viswanadh; Muthukrishnan, M. (New Journal of Chemistry, 2019)
A simple and efficient enantioselective synthesis of anti-obesity drug lorcaerin starting from easily accessible 3-chlorostyrene oxide has been described for the first time employing hydrolytic kinetic resolution as a source of chirality. The protocol might also be useful in the synthesis of structural variants of lorcaserin.

Oxone promoted dehydrogenative Povarov cyclization of N-aryl glycine derivatives: an approach towards quinoline fused lactones and lactams - More, Devidas A.; Shinde, Ganesh H.; Shaikh, Aslam C.; Muthukrishnan, M. (RSC Advances, 2019)
Oxone promoted intramolecular dehydrogenative imino Diels-Alder reaction (Povarov cyclization) of alkyne tethered N-aryl glycine esters and amides has been explored, thus affording biologically significant quinoline fused lactones and lactams. The reaction is simple, scalable, and high yielding (up to 88%). The method was further extended to prepare biologically important luotonin-A analogues and the quinoline core of uncialamycin.

Metal- and light-free direct C-3 ketoalkylation of quinoxalin-2(1H)-ones with cyclopropanols in aqueous medium - More, Devidas A.; Mujahid, M.; Muthukrishnan, M. (ChemistrySelect, 2022)
Direct oxidative C-3 ketoalkylation of quinoxalin-2(1H)-ones with cyclopropanols using ammonium persulfate in an aqueous medium has been achieved in a moderate to good yield. The reaction does not require metals, light-source, or catalysts to facilitate the reaction and could be efficiently utilized to construct a wide range of biologically relevant 3-ketoalkylated quinoxalin-2(1H)-ones.
Keywords: aqueous medium; cyclopropanols; ketoalkylation; metal-free; quinoxalin-2(1H)-ones

Metal-free aminocarbonylation of p-quinone methides with isocyanides: synthesis of sterically hindered alpha-arylated acetamides - Shirsath, Sachin R.; More, Devidas A.; Muthukrishnan, M. (Chemistry-an Asian Journal, 2022)
The synthesis of sterically hindered alpha-arylated acetamides generally requires a multistep reaction sequence and is also difficult to access due to steric constraints. This protocol allows the synthesis of sterically hindered alpha-arylated acetamides in moderate to high yields via 1,6-addition of isocyanides to p-quinone methides in the presence of BF3 center dot OEt2. The present transformation features transition metal-free conditions, avoiding the use of toxic carbon monoxide, broad substrate scope, mild reaction conditions, and operational simplicity.
Keywords: Aminocarbonylation; Isocyanide; p-Quinone methide; Sterically Hindered alpha-Arylated Acetamides

BF3.Et2O-catalyzed selective C-4 alkylation of isoquinolin1(2H)-ones employing p-quinone methides - More, Devidas A.; Ghotekar, Ganesh S.; Muthukrishnan, M. (Chemistry-an Asian Journal, 2023)
The direct C-4 alkylation of isoquinolin-1(2H)-one moiety is a challenging transformation in organic synthesis. Here we present a practical and efficient synthesis of C-4 alkylated isoquinolin-1(2H)-ones through conjugate addition of isoquinolin-1(2H)-ones to p-quinone methides for the first time. The process is facilitated by Lewis acid catalysis and this operationally straightforward, mild, metal-free and one-pot transformation provides a wide range of C-4 alkylated isoquinolin-1(2H)ones at ambient temperature in good to excellent yields.

Metal- and photocatalyst-free, visible-light-initiated C3 a-aminomethylation of quinoxalin-2(1H)-ones via electron donor-acceptor complexes - More, Devidas A.; Shirsath, Sachin R.; Muthukrishnan, M. (Journal of Organic Chemistry, 2023)
We report a metal- and photocatalyst-free C3 a-aminomethylation of quinoxalin-2(1H)-ones with N-alkyl-N-methylanilines. The reaction proceeds through the formation of a photoactivated electron donor-acceptor complex between quinoxalin-2(1H)-ones and N-alkyl-N-methylanilines. The present method provides a mild and environmentally friendly protocol that exhibits good atom economy and excellent functional group tolerance to obtain a library of biologically significant C3 a-aminomethylated quinoxalin-2(1H)-ones in good yields.

Visible-light mediated C-3 amination of quinoxalin-2(1H)-ones via electron donor-acceptor complexation - More, Devidas A.; Gayathri, P. R.; Thete, Kishor R.; Muthukrishnan, M. (Asian Journal of Organic Chemistry, 2024)
The formation of carbon-nitrogen bonds holds paramount importance in the realm of synthetic organic chemistry, finding extensive applications in the synthesis of pharmaceuticals, agrochemicals, and organic materials. Herein, we describe a novel EDA complex mediated, metal- and photocatalyst-free, visible-light-initiated direct C-3 amination of biologically important, quinoxalin-2(1H)-one moiety. The key to the success lies in the formation of a photoactivated electron donor-acceptor complex between quinoxalin-2(1H)-one and amine, which undergo subsequent electron transfer reaction to effect the desired transformation. A diverse array of 3-aminoquinoxalin-2(1H)-ones were prepared employing this process and the yields are up to 87%. This work represents a significant advancement toward a more environmentally friendly and efficient approach, characterized by mild reaction conditions and a high atom economy.
Keywords: C-3 amination; Dehydrogenative amination; EDA complex; quinoxalin-2(1H)-ones